Enabling Collaborative Musical Activities through Wireless Sensor Networks - Santiago J. Barro; Tiago M. Fernández-Caramés; Carlos J. Escudero (International Journal of Distributed Sensor Networks)
In professional audio production the setup of electronic musical devices is a time-consuming and error-prone process, as it involves manual operations like establishing local configurations and carrying cables for each device. Such is the case of MIDI (musical instrument digital interface), which is widely used in the context of musical applications. On the other hand, the capabilities of WSN (wireless sensor networks) allow developers to build up more complex applications, since nodes have the ability of autoidentifying, autoconfiguring, and establishing associations with other nodes, behaving in a smarter way than other networks. In this paper, we propose the use of an optimized WSN network for interconnecting MIDI devices. This network has been named collaborative musical wireless network (CMWN): it eases device configuration, enables musical collaboration, and allows artists to explore new ways of expression. The paper also presents the hardware and performance results of a prototype able to create CMWNs.